The Growth Of Oil Palm (Elaeis guineensis Jacq..) On Media Planting In The Form Of Subsoil, Empty Fruit Branch Of Oil Palm (Efbop) Compost And Rice Husks In Main-Nursery Stage - Bilman Wilman Simanihuruk; Ismail Ismail; Abimanyu Dipo Nusantara (University of Prof. Dr. Hazairin, SH, 2021)
The objectives of this research is to determine the composition of the planting media in the form of subsoil, empty fruit branch of oil palm (EFBOP) compost, and rice husks in the main-nursery. This research was conducted from June 2020 to September 2020 on Jl. Ciptabaru, Pematang Governor's Village, Muara Bangkahulu District, Bengkulu City, Bengkulu Province with an altitude of ±10 meters above sea level. This study used a completely randomized design (CRD) with one factor and three replications, which consisted of 11 treatments, namely M0 (100% Topsoil), M1 (100% Subsoil), M2 (80% Subsoil + 20% EFBOP Compost), M3 ( 80% Subsoil + 20% Rice Husk), M4 (60% Subsoil + 20% EFBOP Compost + 20% Rice Husk), M5 (60% Subsoil + 10% EFBOP Compost + 30% Rice Husk), M6 (60% Subsoil + 30 %EFBOP Compost + 10% Rice Husk), M7(60% Subsoil + 40% EFBOP Compost), M8(60% Subsoil + 40% Rice Husk), M9(50% Subsoil + 50% EFBOP Compost), M10 (50% Subsoil + 50% Rice Husk). Data were analized using Analysis of Variance and continued by Duncan’s Multiple Range Test at the 5% significance level. The result showed that the best planting medium is 50% subsoil + 50% EFBOP compost which produces a stem diameter of 51.02 mm, a total leaf area of ??8094.71 cm2, a greenish level of 59.15 , a dry shoot weight of 129.38 g, a dry root weight of 27.53 g.